Eretmocerus eremicus a new whitefly parasitoid found in New Zealand - Workman, P.J.; Scott, I.A.W.; Drayton, G.M. (New Zealand Plant Protection, 2008)
In the summer of 200607 unsprayed vegetable crops in the Auckland region were surveyed to locate and identify natural enemies of whitefly thrips and psyllids that could be used as biological control agents for pests of greenhouse crops A natural enemy that was specifically sought was a yellow parasitoid of greenhouse whitefly Trialeurodes vaporariorum that had previously been observed in the Auckland region in greenhouse crops (T Marais pers comm) This parasitoid was identified in 1997 by Dr J Berry (Landcare Research) as Eretmocerus sp The 200607 survey located three populations of a yellow parasitoid of greenhouse whitefly on runner beans in a home garden at Waimauku in an organic garden in Silverdale and on greenhouse tomatoes in Mangere Sequences of diagnostic COII ITS2 and D3 gene regions were obtained from the Waimauku samples and subsequent interrogation of sequence databases using BLAST identified the parasitoid as Eretmocerus warrae (Naumann and Schmit 2000) (Hymenoptera Aphelinidae) Eretmocerus warrae was found across the southern half of Australia in surveys in 199597 and is considered endemic to Australia but has only been found from the exotic greenhouse whitefly In 2008 specimens of Eretmocerus collected in 1997 and 2006 were examined by CSIRO and were considered to be morphologically identical It was concluded that both samples of the parasitoids were Eretmocerus eremicus which is now considered to be synonymous with E warrae